2019
DOI: 10.26444/aaem/105390
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages, phage endolysins and antimicrobial peptides – the possibilities for their common use to combat infections and in the design of new drugs

Abstract: The antibiotic resistance in many pathogenic bacteria has become a major clinical problem, therefore, the necessity arises to search for new therapeutic strategies. The most promising solution lies in bacteriophages, phage endolysins and antimicrobial peptides. The aim of this study is to review the possibilities for the common use of bacteriophages, phage endolysins and antimicrobial peptides, both in the form of combined therapies and new strategies for the production of peptide drugs. Bacteriophages are vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 78 publications
0
25
0
2
Order By: Relevance
“…Nonetheless, it is likely that, as is the case of other antimicrobials, the existence of synergy will depend on the specific phage-protein combination and the bacterial strain. There are several studies reporting the existence of synergy between either phages or phage lytic proteins with antibiotics 36 38 , 41 43 . In some cases, such combinations were able to reduce the biofilm population depending on the antibiotic and its concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is likely that, as is the case of other antimicrobials, the existence of synergy will depend on the specific phage-protein combination and the bacterial strain. There are several studies reporting the existence of synergy between either phages or phage lytic proteins with antibiotics 36 38 , 41 43 . In some cases, such combinations were able to reduce the biofilm population depending on the antibiotic and its concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy is the combination of multiple phages targeting different receptors in a single phage preparation, known as a phage cocktail 39 , 40 . Phage lytic enzymes have also been combined with other antimicrobials like antibiotics 41 43 or used as part of a multi-enzyme approach by mixing them with depolymerases, which target polysaccharides such as those present in the extracellular matrix of biofilms 44 . However, to our knowledge, no study has found synergistic effects between phages and lytic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…PGHs have become extensively studied for 20 years, e.g., [11,15,17,53,54,59,61,[63][64][65]67,69,82,106,[141][142][143][144]148,. They can be easily identified and prepared as pure recombinant proteins and have proven to be efficient in killing bacteria, including multidrug-resistant variants [231][232][233][234].…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…Therefore, approximately 20 years ago, researchers started to explore phage-encoded antibacterial enzymes that can overcome some of these phage-therapy limitations. A comparison of the typical attributes of antibiotics, phages, PSDs, and PGHs [ 18 , 24 , 27 , 30 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] is found in Figure 2 . Importantly, manufacturing PSDs and PGHs should not pose many hurdles since large scale recombinant protein production and purification strategies are well established.…”
Section: Phage Enzymes As the Basis Of New Antibacterial Therapiesmentioning
confidence: 99%
See 1 more Smart Citation